2022
DOI: 10.1155/2022/8270137
|View full text |Cite|
|
Sign up to set email alerts
|

Effect Analysis of Clinical Pathway Nursing Combined with Humanized Nursing in Cerebral Infarction

Abstract: Objective. To make the application effect of clinical pathway nursing combined with humanized nursing clear in cerebral infarction. Methods. Hundred patients who suffered from cerebral infarction had been hospitalized in our hospital and they become our study objects. By means of the random number table, they were separated into 50 cases both in the control group and in the observation group. The control group accepted the routine nursing, and the observation group accepted the clinical pathway nursing mixed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…It can also increase patients' knowledge of the efficacy of self-treatment, minimizing complications, and poor prognosis. In the study of Xiao et al [23] on cerebral infarction, it was suggested that the application of CNP can reduce complications and recurrence, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…It can also increase patients' knowledge of the efficacy of self-treatment, minimizing complications, and poor prognosis. In the study of Xiao et al [23] on cerebral infarction, it was suggested that the application of CNP can reduce complications and recurrence, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…El trato humanizado ayuda a reducir el estrés de los pacientes; por lo tanto, los profesionales de la salud deben ser humanos no solo en el conocimiento, sino también en el desempeño técnico. Es así, que se puede destacar ciertos pensamientos que tiene el personal de salud al brindar un trato humanizado a sus pacientes; tratar bien a las personas, ser humanos con el paciente, recibir de la mejor manera al paciente en el quirófano para que se sientan bien y tranquilos ( Xiao et al,2022), es así, que el concepto de humanización es entendido cómo poner más emoción en el cuidado prestado, escuchar e integrar tanto al equipo médico como al de enfermería para socializar informaciones sobre los pacientes y comprenderlos mejor, libres de estereotipos y discriminaciones. Esta humanización se puede lograr integrando el conocimiento de sus conceptos básicos y el cultivo de nuevas costumbres e ideologías (He et al,2022).…”
Section: Resultsunclassified
“…This model aims to deliver patients safe, high-quality, satisfactory, and comprehensive nursing services[ 4 ]. In addition, the precision rehabilitation nursing model for chronic disease management has been reported to exhibit potential value and advantages in emergency department nursing, highlighting the potential for the standardization of the emergency nursing process and path to prevent errors and improve nursing efficiency[ 5 ].…”
Section: Introductionmentioning
confidence: 99%